Oxidized Bacterial Cellulose Membranes Immobilized with Papain for Dressing Applications: Physicochemical and In Vitro Biological Properties - Niédja Fittipaldi Vasconcelos; Pascale Chevallier; Diego Mantovani; Morsyleide de Freitas Rosa; Fernando José Soares Barros; Fábia Karine Andrade; Rodrigo Silveira Vieira (MDPI AG, 2024)
This research consolidates our group's advances in developing a therapeutic dressing with innovative enzymatic debridement, focusing on the physicochemical and in vitro biological properties of papain immobilized in wet oxidized bacterial cellulose (OxBC-Papain) dressing. OxBC membranes were produced with Komagataeibacter hansenii oxidized with NaIO4, and papain was immobilized on them. They were characterized in terms of enzyme stability (over 100 days), absorption capacity, water vapor transmission (WVT), hemocompatibility, cytotoxicity, and cell adhesion. The OxBC-Papain membrane showed 68.5% proteolytic activity after 100 days, demonstrating the benefit of using the OxBC wet membrane for papain stability. It had a WVT rate of 678 g/m2·24 h and cell viability of 99% and 86% for L929 and HaCat cells, respectively. The membranes exhibited non-hemolytic behavior and maintained 26% clotting capacity after 1 h. The wet OxBC-Papain membrane shows significant potential as a natural biomolecule-based therapeutic dressing for wound care, offering efficient debridement, moisture maintenance, exudate absorption, gas exchange, and hemostasis without cytotoxic effects or cell adhesion to the dressing. Further research, especially using in vivo models, is needed to assess its efficacy in inducing epithelialization. This study advances stomatherapy knowledge, providing a cost-effective solution for enzymatic debridement in healthcare.